2015
DOI: 10.1017/jfm.2015.279
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of leading-edge vortex circulation in samara-like flight

Abstract: As an abstraction of natural samara flight, steadily rotating plates in a free-stream flow have been studied. Particle image velocimetry on span-normal planes has been conducted to show that increasing rotation, as captured by the dimensionless parameter of tip speed ratio, causes a transition of the mean wake topology from that of a bluff body to that of a stable leading-edge vortex. Despite its notable effect on topology, a change in tip speed ratio has negligible effect on leading-edge circulation at a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Nonetheless, although DPIV allows to study the flow field, the force distribution is not easily measured experimentally. Consequently, force distributions are usually extrapolated from the velocity field as in Lentink et al (2009), Salcedo et al (2013) and Limacher and Rival (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, although DPIV allows to study the flow field, the force distribution is not easily measured experimentally. Consequently, force distributions are usually extrapolated from the velocity field as in Lentink et al (2009), Salcedo et al (2013) and Limacher and Rival (2015).…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental studies on the flight dynamics and aerodynamics of samara seeds have been reported in literature (e.g. (2,3,32,33) ). These studies were carefully analysed to obtain a good insight into the construction of the proper experimental setup for the purpose of achieving the objectives of this validation study.…”
Section: Wind Tunnel Experimentsmentioning
confidence: 99%
“…2008; Lentink et al. 2009; Limacher & Rival 2015; Bottom II et al. 2016), and in engineering – on rotorcraft (Carr 1988; Corke & Thomas 2015), wind turbines (Schreck & Robinson 2005), swept and delta wings (Maltby 1968; Hitzel & Schmidt 1984; Gursul, Gordnier & Visbal 2005), micro-air vehicles (Ellington et al.…”
Section: Introductionmentioning
confidence: 99%
“…Vortex shedding from the leading edges of foils, wings and rotor blades have been observed in nature -on swimming and flying animals and seeds (Ellington et al 1996;Taylor, Nudds & Thomas 2003;Muijres et al 2008;Limacher & Rival 2015;Bottom II et al 2016), and in engineering -on rotorcraft (Carr 1988;Corke & Thomas 2015), wind turbines (Schreck & Robinson 2005), swept and delta wings (Maltby 1968;Hitzel & Schmidt 1984;Gursul, Gordnier & Visbal 2005), micro-air vehicles (Ellington et al 1996;Ellington 1999) and flapping-wing energy-harvesting devices (Young, Lai & Platzer 2014). Many investigations of leading-edge-vortex (LEV) formation and shedding from airfoils in two-dimensional flow have revealed the connection between the onset of separation and/or vortex formation at the leading edge and its dependence on leading-edge radius and Reynolds number (McCullough & Gault 1951;Gault 1957; it was shown that, for unsteady airfoils undergoing high-rate motions, the initiation of LEV formation occurs when the instantaneous value of the LESP reaches a critical value, termed LESP crit .…”
Section: Introductionmentioning
confidence: 99%